Pengembangan Rumah Imunisasi dengan My Board in the Village - Naimah, Naimah; Triningsih, Reni Wahyu; mas'udah, endah kamila (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2023)
Complete basic immunization is an immunization organized by the government which aims to improve the health status of infants in Indonesia, which is given starting from infants aged 0 to. 18 months. The data shows that the complete basic immunization coverage in Malang Regency is still below the minimum target. The success of fulfilling this coverage cannot be separated from the role of health kader as a bridge between health workers and immunization targets in particular. This community service aims to socialize and train health kader in using the "My Board in the Village" immunization monitoring board in Gondowangi village, Malang Regency. The method of community service activities is divided into 5 sessions, namely 2 sessions for socialization activities using the lecture, discussion, question and answer method, and 3 sessions for demonstrations and redemonstrations by health kader. The results of the activities of all Health kader in Gondowangi village, Malang Regency can demonstrate the procedure for using “My Board in the Village” Immunization House Development with “My Board in the Village” is an activity to empower health kader which should be carried out continuously in collaboration with related parties, so that it is expected to contribute to the realization of an increase in the degree of public health in general and children in particular.